Chapter A proposito di quantificatori indefiniti di massa in polacco - Cotta Ramusino, Paola (Biblioteca di Studi Slavistici, 2016)
The present paper examines substandard Polish constructions in which the quantifiers kupa 'a lot', masa 'mass' and połowa 'a half' in Subject function occur in the Accusative case (plus the referential noun in the Genitive) and take neuter singular verb agreement: Kupę ludzi zebrało się na placu, 'a lot of people gathered in the square'. Drawing on a large amount of occurrences taken from two corpora a qualitative analysis of the construction is carried out, in order to highlight how the indefinite quantifier semantic characteristics predispose it to the thematic role of Patient.